Arterial fragility in kyphoscoliotic Ehlers-Danlos syndrome. (6th July 2018) - Henneton, Pierrick; Legrand, Anne; Giunta, Cecilia; Frank, Michael
Abstract : Pathogenic variants in the lysyl-hydroxylase-1 gene (PLOD1) are responsible for the kyphoscoliotic type of Ehlers-Danlos syndrome (EDS). The disease is classically responsible for severe hypotonia at birth, progressive kyphoscoliosis, generalised joint hypermobility and scleral fragility. Arterial fragility is an important feature of the disease, but its characterisation remains limited. We report the clinical history of a 41-year-old woman who presented repeated arterial accidents, which occurred in previously normal medium size arteries within a limited time span of 2 years. Molecular investigations revealed compound heterozygosity for two PLOD1 gene deletions of exons 11–12 and 14–15. Arterial fragility is an important characteristic of kyphoscoliotic EDS. It manifests as spontaneous arterial rupture, dissections and dissecting aneurysms which may occur even during early childhood. This fragility is particularly likely to manifest during surgical intervention. Early medical management and surveillance may be indicated, but its modalities remain to be defined.